THE LIVING PHILOSOPHY OF TUMPENG: PRESERVING JAVANESE CULTURAL IDENTITY IN THE MODERN ERA - Syahputra, Heru; Nasution, Hasyimsyah; Drajat, Amroeni (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: This study explores the living philosophy, cultural significance, and resilience of the tumpeng tradition as part of Javanese cultural identity in the context of modernization and globalization. Framed within the broader discourse of cultural heritage, the research highlights how tumpeng is more than a ceremonial dish; it symbolizes local wisdom and civic values through its conical shape, color, and carefully selected side dishes that together reflect gratitude, balance, humility, and spiritual devotion. Purpose: The study aims to examine how these meanings are transmitted across generations and the challenges posed by changing lifestyles, urbanization, and the rise of global consumer culture. Method: Using a qualitative descriptive approach grounded in literature review and cultural analysis, the article finds that the practice of preparing and sharing tumpeng functions as an intergenerational educational process that sustains communal bonds and ethical reflections, keeping cultural memory alive as an ongoing practice rather than a fixed inheritance. Result: However, the continuity of this tradition is threatened when younger generations perceive it as outdated or when rituals are performed without understanding their deeper philosophical context. Conclusion: The study concludes by suggesting adaptive strategies such as integrating cultural education in formal and informal contexts, promoting storytelling and community workshops, and using the creative economy to engage youth while maintaining authenticity. Ultimately, the findings reaffirm that tumpeng endures as a living cultural practice that not only preserves local wisdom but also offers ethical guidance for navigating modern life.